2018
DOI: 10.1093/mnras/sty2935
|View full text |Cite
|
Sign up to set email alerts
|

Discovering AGN-driven winds through their infrared emission – I. General method and wind location

Abstract: Large scale outflows of different gas phases are ubiquitous in the host galaxies of active galactic nuclei (AGN). Despite their many differences, they share a common property -they all contain dust. The dust is carried with the outflow, heated by the AGN, and emits at infrared wavelengths. This paper shows that the infrared emission of this dust can be used to detect AGN outflows and derive their properties. We use a sample of ∼4 000 type II AGN and compare the infrared properties of systems that show spectros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 89 publications
(135 reference statements)
5
37
0
Order By: Relevance
“…In addition, looking at both our sample and other, often larger, AGN samples (e.g. Baron & Netzer 2019a;Davies et al 2020), the derived values of the ionisation parameter typically change by less than an order of magnitude across each sample. For this reason, we believe that the errors on U are playing a minor role, and attribute the discrepancy between the densities mainly to the uncertainties on the derived L BOL and outflow radii.…”
Section: Appendix C: Comparison With the E(b-v) And N E Measured Withmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, looking at both our sample and other, often larger, AGN samples (e.g. Baron & Netzer 2019a;Davies et al 2020), the derived values of the ionisation parameter typically change by less than an order of magnitude across each sample. For this reason, we believe that the errors on U are playing a minor role, and attribute the discrepancy between the densities mainly to the uncertainties on the derived L BOL and outflow radii.…”
Section: Appendix C: Comparison With the E(b-v) And N E Measured Withmentioning
confidence: 84%
“…On the other hand, in "quasar mode" feedback, the outflows driven by radiatively efficient AGN act to heat and expel the pre-existing cooler gas in the host galaxies that would otherwise form stars. The range of radial scales over which this form of feedback operates is currently controversial, with estimates ranging from tens of pc to >10 kpc (Greene et al 2012;Harrison et al 2012Harrison et al , 2014Liu et al 2013;Husemann et al 2016;Villar-Martín et al 2016;Tadhunter et al 2018;Revalski et al 2018;Fischer et al 2018; Baron & Netzer 2019a). Although this feedback mode is often linked to winds driven by the radiation pressure of the central AGN (King & Pounds 2015), relativistic jets may play a significant role, even in cases in which the radio luminosity is relatively modest (L 1.4 GHz < 10 24 W Hz −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported ubiquitous outflow sizes of several kpc scales (e.g. Harrison et al 2014;McElroy et al 2015;Liu et al 2013a,b), but recently much lower outflow sizes of <1 kpc were reported in several studies (Husemann et al 2016a;Villar-Martín et al 2016;Tadhunter et al 2018; Baron & Netzer 2019). The difference may partially be explained due to the effect of beam smearing in seeing-limited observations (Husemann et al 2016a).…”
Section: Introductionmentioning
confidence: 95%
“…This does not approach the 5.0 × 10 −3 -5.0 × 10 −2 range used in models of efficient feedback (Di Matteo et al 2005;Hopkins & Elvis 2010). The low ratios of / were also found in other samples by Baron & Netzer (2019) and Davies et al (2020), however, these are much less than those derived from Figure 10. For a majority of our sample, it is possible to see a relation between the maximum outflow rate and (left panel) and the position where the peak outflow rate occurs and the maximum outflow rate for each target (right panel).…”
Section: Discussionmentioning
confidence: 52%
“…The In order to account for the grain composition, we include depletions from gas phase for C, O and the refractory elements (e.g., Snow & Witt 1996). Note that dust can play an important role in the dynamics of outflows (e.g., Baron & Netzer 2019). We will be examining the outflow dynamics in our subsequent paper (Trindade Falcão et al in preparation).…”
Section: Photoionisation Models and Constraints On Gas Densitymentioning
confidence: 99%